Larry and the meaning of life [compact disc, unabridged] - Tashjian, Janet (Random House/Listening Library, 2008)
Larry (otherwise known as Josh) is in the doldrums, but after meeting a spiritual guru at Walden Pond who convinces him to join his study group, he starts to question his grasp of reality.